Production Forecast Studies for Oil Well Performance Prediction and Field De-velopment Scenario Using Decline Curve Analysis in Multilayer Reservoirs: A Case Study of Field Z - Cahyadi Julianto; Hidayat Tulloh; Aldi Priambodo; Muhammad Rizky Nugroho; Haykal Kurniawan (Future Science)
Field Z is located in the south Sumatra region with a reservoir located in the Talang Akar and Baturaja formation. Field Z has 9 layers and 29 wells have been produced until 2019. Based on the calculation of the JJ Arps method (water drive), the recovery factor of Layer 1 is 42,834%, RF layer 2 is 42.62% and layer 6 is 40.16%. This Arps can be estimated how much oil can be produced from OOIP owned by the reservoir. From these results obtained volumetric In-Place magnitude at Layer 1 = 11.52 MMSTB, Layer 2 = 17.99 MMSTB, and Layer 6 = 7.50 MMSTB. But the recovery factor of the Z field is currently only 9.67% in the last year of 2019. From this statement, it is necessary to develop a field development scenario. The method in this paper is to take data from the field and then the data is processed to forecast production using a decline curve analysis (DCA) using Oil Field Management software. After forecasting production, a scenario is then performed to extend the production life of the well.